Studi Komparasi Pemikiran Ibnu Taimiyah dan John Maynard Keynes Tentang Keuangan Publik - Minarni Minarni (Jurnal Ilmiah Ekonomi Islam, 2021)
This article examines Ibn Taimiyyah’s thoughts in Islamic Public Finance as contained in several of his books, including the book Majmu’ Fatawa, Al-Siyasah al-Syar’iyyah fi Islah al-Ra’i wa al-Ra’iyyah and the book Al-Hisbah fi al-Islam aw Wazifah al-Hukumah al-Islamiyah. Furthermore, these thoughts are compared with the concept of fiscal policy proposed by John Maynard Keynes in his book The General Theory of Interest and Money. This research is literature study using comparative methods and qualitative descriptive analysis. The results of this study indicate that Ibn Taymiyyah’s thoughts on public finance have the advantage of Islamic values based on the Qur’an and the Sunnah, upholding the values of justice, is oriented towards material and spiritual welfare, the existence of a hisbah institution which acts as a supervisor, sources of state revenue paying attention to the aspects of halalness, emphasizing the zakat sector and managing of public ownership. As far the allocation of state expenditures in accordance with the provisions of Islamic law and the benefit of the people. Whereas Keynes fiscal policy is based on man-made regulations, emphasizes state revenue from the tax sector, and is oriented towards material welfare. However, the two concepts have similarities in several state expenditure allocations, including defense and security costs, salaries of state officials, and construction of public facilities. In addition, there are similarities, the role of the state in overcoming unemployment and alleviating poverty.